Case Report: Endoscopic ultrasound-guided fine-needle biopsy for the diagnosis of esophageal tuberculosis - Yang, Hailin; Ke, Huajing; Lei, Yupeng; Zhu, Yong (Frontiers in Medicine, 2025)
AimTo summarise the characteristics of esophageal tuberculosis, and to evaluate the role of endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) in the diagnosis of esophageal tuberculosis.MethodsA retrospective analysis of esophageal tuberculosis patients diagnosed by the EUS-FNB between May 2012 and August 2023 was reported. Final diagnosis was based on histopathology, clinical context in combination with response to antitubercular therapy. Tissue acquisition of both esophageal lesions and enlarged mediastinal lymph nodes was performed by EUS-FNB. The variables evaluated were clinical features, location and diameter of the esophageal lesions and enlarged lymph nodes.ResultsSix esophageal tuberculosis patients without surgical management were finally identified by the performance of EUS-FNB. The most common clinical feature was progressive dysphagia. The site of lesions was most common located in the middle of esophagus (66.7%). Diameter of lesions range from 1.2 to 4.1 cm. Multiple enlarged mediastinal lymph nodes were of various sizes (range 0.6–1.6 cm in diameter). CT scan revealed focal thickened esophageal wall, esophageal stenosis, and a mass with moderate and heterogeneous enhancement in five patients (83.33%), which indicating esophageal carcinoma. Purified protein derivative (PPD) and T cell spot test (T-spot) were positive in four cases (66.7%), which were significant in the diagnosis. EUS-FNB provided the pathological diagnosis of tuberculosis in four cases.ConclusionEsophageal tuberculosis should be distinguished from advanced esophageal carcinoma and leiomyoma. Moreover, EUS-FNB is an excellent method in both image and tissue biopsy to establish an accurate diagnosis of esophageal tuberculosis.